Admission control and scheduling for improved QoS provisioning in transport and access networks - Xue, Daojun (2009)
The increasing popularity of new multimedia services has made it desirable to support end-to-end Quality-of-Service (QoS) provisioning across multiple network domains. It is a very challenging problem and there is little progress in an implementable solution so far. Instead of providing a full solution at this stage, our goal in this thesis work is to implement QoS guarantees in each individual network that a user connection passes (e.g. transport networks and access networks), which is the necessary condition for an overall inter-networking QoS architecture.